Enhancing efficiency of perovskite solar cell via surface microstructuring: superior grain growth and light harvesting effect - Tathavadekar, Mukta C.; Agarkar, Shruti A.; Game, Onkar S.; Bansode, Umesh P.; Kulkarni, Sneha A.; Mhaisalkar, Subodh G.; Ogale, Satishchandra B. (Solar Energy, 2015)
We have introduced a novel approach to enhance the perovskite solar cell efficiency by controlling the grain growth and light harvesting properties of perovskite crystallites. Instead of using a mesoporous TiO2 layer, we have modified the surface microstructuring of the TiO2 film by dispensing nano assembled TiO2 submicron structures (nanobeads, NBs) on TiO2 compact layer. With this new approach solar cell efficiency was improved significantly through an increase in both J(sc) and V-oc. This high efficiency is attributed to crystallite size of the perovskite phase. These also act as light scattering centers giving higher current density and reduced recombination effects giving higher open circuit voltage. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: Grain growth; Light harvesting; Perovskite solar cells; TiO2 nanobeads

Dual-functional 3-acetyl-2,5-dimethylthiophene additive-assisted crystallization control and trap state passivation for high- performance perovskite solar cells - Saykar, Nilesh G.; Iqbal, Muzahir; Pawar, Mahendra; Chavan, Kashinath T.; Mahapatra, Santosh K. (ACS Applied Energy Materials, 2022)
Defect-mediated charge recombination and successive degradation mainly lag the performance of perovskite solar cells (PSCs). Insufficiency or evaporation of organic cations leaves behind the undercoordinated Pb2+ ions, which act as severe charge recombination centers. Herein, theoretical and experimental insights into crystallization control and defect passivation of MAPbI3 perovskite by the dual-functional 3-acetyl-2,5-dimethylthiophene (ADT) molecule are pre-sented. Density functional theory calculations show that both functional groups of ADT possessing different interaction energies could interact with PbI2. The carbonyl group in ADT shows the dominant interaction with Pb2+ forming an intermediate product that might decrease the crystallization rate. Further, the coordinate bonding between ADT and uncoordinated Pb2+ ions in perovskite leads to defect passivation. The 0.6% ADT-modified PSCs possess an average power conversion efficiency (PCE) of 18.22 +/- 0.80% and the highest PCE of 19.03%, whereas the pristine PSCs exhibit an average PCE of 16.23 +/- 1.32% and the highest PCE of 17.47%. Furthermore, the modified PSCs maintain 80% of the initial PCE up to 650 h during storage at ambient conditions (RH = 35 +/- 5%). The present study shows that the simultaneous crystalization control and defect passivation achieved via an ADT additive engineering approach could be an efficient strategy to enhance the PCE and stability of PSCs.
Keywords: 3-acetyl-2; 5-dimethylthiophene; additive engineering; crystallization control; defect passivation; Perovskite solar cells

Chemical bridge-mediated heterojunction electron transport layers enable efficient and stable perovskite solar cells - Patil, Pramila; Maibam, Ashakiran; Sangale, Sushil S.; Mann, Dilpreet Singh; Lee, Hyun-Jung; Krishnamurty, Sailaja; Kwon, Sung-Nam; Na, Seok-In (ACS Applied Materials and Interfaces, 2023)
Perovskite solar cells (PSCs) emerged as potential photovoltaicenergy-generating devices developing in recent years because of theirexcellent photovoltaic properties and ease of processing. However,PSCs are still reporting efficiencies much lower than their theoreticallimits owing to various losses caused by the charge transport layerand the perovskite. In this regard, herein, an interface engineeringstrategy using functional molecules and chemical bridges was appliedto reduce the loss of the heterojunction electron transport layer.As a functional interface layer, ethylenediaminetetraacetic acid (EDTA)was introduced between PCBM and the ZnO layer, and as a result, EDTAsimultaneously formed chemical bonds with PCBM and ZnO to serve asa chemical bridge connecting the two. DFT and chemical analyses revealedthat EDTA can act as a chemical bridge between PCBM and ZnO, passivatedefect sites, and improve charge transfer. Optoelectrical analysisproved that EDTA chemical bridge-mediated charge transfer (CBM-CT)provides more efficient interfacial charge transport by reducing trap-assistedrecombination losses at ETL interfaces, thereby improving device performance.The PSC with EDTA chemical bridge-mediated heterojunction ETL exhibiteda high PCE of 21.21%, almost no hysteresis, and excellent stabilityto both air and light.
Keywords: charge transfer; chemical bridge; electron transport layer; ethylenediaminetetraacetic acid; Perovskite solar cells; trap-assisted recombination